Sustainable Concrete Columns with GGBS and Industrial Sand: A Comparative Study on Destructive and Nondestructive Tests on Damaged Columns Strengthened with GFRP Jacketing - G. I. Gunarani; B. Karthikeyan; A. Priyadharshini; Senthil Kumaran Selvaraj; S Jose; D. Vincent Herald Wilson; Tezeta Moges Adane (Advances in Civil Engineering)
This paper presents the experimental investigation of the load-resisting characteristics of damaged columns repaired with glass reinforced polymer (GFRP) jacketing. The high-strength columns were made with ground granulated blast furnace slag (GGBS) used at 15%, 25%, and 35% as a partial substitute for cement. Cube specimens of size 100 mm × 100 mm × 100 mm and columns of size 600 mm × 120 mm were cast to perform the study. Considering the practical difficulties in the construction field in obtaining river sand, industrial sand was used for making the specimens eco-friendly. On completion of the prescribed curing period of 28 days, the cube specimens were subjected to a compression test to ensure the grade of the mix design, and the column specimens were subjected to axial loading and were tested in two categories, with and without wrapping of GFRP sheets’ split tensile strength. Compression tests on cubes and columns were done. The nondestructive test was also performed with the ultrasonic pulse velocity (UPV) method to check the dense nature of the concrete before and after wrapping with GFRP. On comparing the results, it was observed that it is possible to obtain a higher strength using industrial sand when supported with suitable admixtures and strengthening processes.